Wanita dan Toleransi Beragama (Analisis Psikologis) - Maimanah, Maimanah (Jurnal Muadalah, 2013)
It has become the responsible of all parties to promote public toleratnce in the mids of religious pluralism in Indonesia. The issue of tolerance is a matter of religious awareness which concerns with the psychological aspect, so that it is significant to present the issue of tolerance with psychological approach. Women as one of the active religious followers have psychological potential to exhibit tolerance. Various roles that women run have coloured themselves with the essence of humanity that all human whatever ethnicity and religion they proclaim are one big family who should live in harmony.Keywords: women, tolerance, psychological, harmony,Adalah menjadi tanggung jawab semua pihak untuk mewujudkan masyarakat yang toleran di tengah pluralitas agama di Indonesia. Persoalan toleransi adalah persoalan kesadaran beragama yang menyangkut aspek psikologis, sehingga penting mengetengahkan isu toleransi dengan pendekatan psikologis. Wanita sebagai salah satu pihak penganut agama aktif memiliki potensi psikologis yang besar untuk berperilaku toleran, berbagai peran yang dijalaninya memberikan wanita makna nilai-nilai kemanusiaan, bahwa semua manusia apa pun agama, suku dan rasnya adalah satu keluarga besar yang bisa hidup dengan harmonis.Kata kunci: wanita, toleransi, psikologis, kekeluargaan, keharmonisan.